The association between circulating leukocytes and inflammatory bowel disease: a two-sample Mendelian randomization study - Tian, Li; Yang, Xiaobin; Zheng, Yansen; Peng, Chaosheng (Frontiers in Medicine, 2024)
Background Inflammatory bowel disease (IBD) is a highly prevalent, recurrent, chronic intestinal inflammatory disease. Several observational studies have shown that circulating leukocytes are strongly associated with IBD. However, whether alterations in leukocytes are causally related to IBD remains uncertain. The present study explores this issue with the Mendelian randomization (MR) analysis method. Methods The Genome wide association study (GWAS) statistical data related to circulating leukocytes and IBD were obtained from the Blood Cell Consortium and the IEU Qpen GWAS project, respectively. Inverse variance weighting (IVW) was used as the main MR analytical method, coupled with a series of sensitivity analyses to ensure the reliability of the results. Results The results of IVW showed that increased monocyte count (especially CD14- CD16+ monocyte absolute counts) was negatively correlated with the risk of IBD and its main subtypes. Increased neutrophil count was positively associated with the risk of IBD and ulcerative colitis. Meanwhile, there was no causal relationship between basophil, eosinophil, lymphocyte counts and IBD risk. Conclusion These results indicate that a causal relationship exists between circulating leukocytes and the risk of IBD and its subtypes, which confirms the important role that the leukocyte immune system plays in IBD. Our findings provide additional research directions for the clinical prevention and treatment of IBD.